Richard Smith diary - Smith, Richard, 1735-1803.
Detailed diary of the proceedings (132 pages), 1775 September 12-October 1; 1775 December 12-1776 March 30, of the Continental Congress, as observed by Smith, member of the Committee on Claims. Subjects include property losses and government expenditures during the Revolutionary War.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Public official of New Jersey and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Congress; United States. -- Continental Congress. -- Committee on Claims; New Jersey -- History -- Revolution, 1775-1783.; New Jersey -- Politics and government -- 1775-1865.; United States -- History -- Revolution, 1775-1783 -- Finance; Lawyers; Public officials -- New Jersey